Prevalence of and factors associated with swellings of the ribs in tie stall housed dairy cows in Germany. - Greta E Abele; Yury Zablotski; Melanie Feist; K Charlotte Jensen; Annegret Stock; Amely Campe; Roswitha Merle; Andreas W Oehm (PLoS ONE, 2022)
Swellings of the ribs result from severe injury and affected animals are subjected to considerable and prolonged pain and suffering. The knowledge on rib swellings in dairy cows has yet been very limited. Therefore, the present study aimed at determining the prevalence of rib swellings in tie stall housed dairy cows in Germany as well as at identifying associated factors. Mean animal-level prevalence of rib swellings for 2,134 cows was 7.54% with a mean of 7.00% on farm level (range 0.00% - 37.49%). Multivariable mixed logistic regression models including nested random effects were built and factors associated with swellings of the ribs were evaluated for 1,740 dairy cows on 96 farms in Germany. Out of the initial 22 predictors, 8 factors were selected for the final model. Managing dairy cows on a part-time basis (OR 0.49 [CI 0.25-0.98]) appeared to decrease the odds for rib swellings compared with full-time farming. Cattle breeds other than Simmental entailed lower odds for rib swellings (OR 0.29 [CI 0.14-0.59]). Lame cows (OR 2.59 [CI 1.71-3.93]) and cows with wounds and/or swellings of the hocks (OR 2.77 [CI 1.32-5.84]) had more than two times the odds for rib swellings compared with sound animals. The results of the present study can help raising awareness of rib swellings in dairy cows and contribute to the body of evidence on this condition.